Mewujudkan Pengembangan Manajemen Perilaku Organisasi Untuk Sumber Daya Manusia Yang Kompeten - Djoko Hananto; Aulia Juniar Putri; Dela Amanda Fitria; Firda Aliyaturrusydah; Muhammad Yuda Ferdiansyah (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2024)
This research covered various aspects of management such as recruitment and development but did not adequately explain how the effectiveness of each step was measured and evaluated empirically. The mismatch of teaching staff with needs and the lack of supervision were the main obstacles in the Madrasah, necessitating increased teacher training and stricter supervision. This research provided a comprehensive overview of organizational behavior management at Madrasah Ibtidaiyah (MI) Darussalam Pacet during the 2017/2018 academic year. The research successfully detailed the management steps implemented, from planning to evaluation, and identified relevant obstacles and solutions. It would have been more beneficial if the research also considered the perspectives of teachers and students regarding the changes implemented and their impact on performance and motivation. This research had significant competence in understanding and addressing the specific challenges occurring in the Madrasah.